Claims and counterclaims: institutional arrangements and farmers' response to the delivery and adoption of innovations in the Okavango Delta, Botswana. Issue 2 (15th March 2017) - Noga, Sekondeko Ronnie; Kolawole, Oluwatoyin Dare; Thakadu, Olekae Tsompi; Masunga, Gaseitsiwe Smollie
ABSTRACT: Purpose: This article examined how institutional factors influencing the promotion of two elephant crop-raiding deterrent innovations (ECDIs) introduced to farmers through a ministry-based extension system in the Okavango Delta, Botswana, have impacted farmers' adoption behaviour. Methodology: A standardised interview schedule was used to elicit responses from 388 randomly sampled subsistence arable farmers on how institutions influenced the adoption of ECDIs in five communities in the study area. This was complemented by focus group discussions to obtain in-depth information on the subject-matter. Key informants interviews were also conducted with purposively selected extension agents, village project committee chairpersons and village dikgosi. Findings: Four institutional factors were found to be critical for the adoption of ECDIs. These include institutional relations, availability and/or supply of deterrent innovation inputs, farmers' contact with extension agents and government support for extension services. Theoretical Implications: Immediate and widespread adoption of ECDIs in the ever-changing socio-economic and political environment can be enhanced by context-specific institutional arrangements in addressing social and organisational constraints to innovation adoption. Originality: This paper invoked organisational theory to contribute to the scholarly debate on how agricultural extension systems influence farming clientele's behaviour and social change. It offers the first attempt in the investigation of the role of extension and associated institutions/organisations in promoting adoption of ECDIs among subsistence farmers in the Okavango Delta, Botswana. Findings indicate that local farmers do not perceive extension agencies to hold monopoly of ideas and solutions to their unique problems.